The Sociology of the Ghetto in James Baldwin's SONNY'S BLUES. Issue 3 (3rd July 2018) - Kim, Eui Young
Abstract: This essay examines the sociological insight embedded in James Baldwin's "Sonny's Blues." Due to Baldwin's compelling portrayal of brotherly estrangement and the difficult process of reconciliation, critics have frequently elided the dense description of the physical setting. Baldwin's sustained attention to the physical features of Harlem, however, arises from his intimate knowledge of the ghetto as social space. This essay close reads Baldwin's extended description of Harlem to reveal the power attributed to the ghetto. Baldwin tracks how disorder spreads from the streets into the buildings and back into the streets, creating a closed circuit of disorder in the neighborhood. Baldwin is equally attentive to how signs of disorder alter human behavior. This observation allows him to counter the sociological idea that the higher crime rate in the ghetto is due to the dysfunctional African American family. In "Sonny's Blues, " Baldwin presents the reality of Harlem that closely approximates the mature understanding of the ghetto that sociologists only gradually arrived at through decades of further research.